Failure Analysis and Prevention 2017
DOI: 10.5772/intechopen.72789
|View full text |Cite
|
Sign up to set email alerts
|

Common Case Studies of Marine Structural Failures

Abstract: Marine structures are designed with a requirement to have reasonably long and safe operational life with a risk of catastrophic failures reduced to the minimum. Still, in a constant wish for reduced weight structures that can withstand increased loads, failures occur due to one or several following causes: excessive force and/or temperature induced elastic deformation, yielding, fatigue, corrosion, creep, etc. Therefore, it is important to identify threats afecting the integrity of marine structures. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Conversely, Opening 3 exhibited a notably different stress distribution pattern, as the concentration of stress appeared to be more evenly spread across the bottom of the opening instead of being localized at a single point around 504.14 MPa, Figure 13. This dispersed stress concentration, while not concentrated in a specific region, still carried the potential to induce failure within that particular area [21], as evidenced by the findings of this study. In addition to the stress concentration effects induced by the openings, it is essential to acknowledge the influence of welding on the joint connecting the stiffener to the plate, as this factor also plays a role in shaping the overall strength and structural behavior of the ship.…”
Section: Discussionsupporting
confidence: 57%
“…Conversely, Opening 3 exhibited a notably different stress distribution pattern, as the concentration of stress appeared to be more evenly spread across the bottom of the opening instead of being localized at a single point around 504.14 MPa, Figure 13. This dispersed stress concentration, while not concentrated in a specific region, still carried the potential to induce failure within that particular area [21], as evidenced by the findings of this study. In addition to the stress concentration effects induced by the openings, it is essential to acknowledge the influence of welding on the joint connecting the stiffener to the plate, as this factor also plays a role in shaping the overall strength and structural behavior of the ship.…”
Section: Discussionsupporting
confidence: 57%
“…Laser vibrometry allows carrying out measurements using a laser beam [ 26 , 27 , 31 , 46 ]. It enables measurements of vibrations in a non-contact and non-invasive way.…”
Section: Methodsmentioning
confidence: 99%
“…SHM systems use a number of advanced sensors, such as fiber Bragg grating (FBG) sensors [ 21 , 22 , 23 , 24 ]. There are also works connected with the application of laser vibrometers in SHM application [ 8 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], but authors have not found any information about the use of such sensors onboard ships.…”
Section: Introductionmentioning
confidence: 99%
“…Various factors of structural failure can cause damage to the ship so that it can affect operations [3]. Marine structures must comply with the design requirements in such a way that the probability of failure can be reduced to a minimum [4] . In addition, the strength of the structure of the ship or marine structure affects the durability of the structure itself.…”
Section: Introductionmentioning
confidence: 99%